PERAN GENDER PEREMPUAN DALAM UPAYA MENCIPTAKAN PERDAMAIAN DEMI MEWUJUDKAN PEMBANGUNAN YANG BERKELANJUTAN DI TINGKAT GLOBAL - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Research using qualitative methods with this type of literature has the aim of knowing the role of women's gender in efforts to create peace and the role of realizing sustainable development at the global level. The results showed that the role of women's gender in creating peace from the countries of Indonesia, Afghanistan, India, Lebanon, Sudan, Pacific Islands, Central African Republic (CAR), Uganda, and Democratic Republic of Congo (DRC) are: (1). Women play a role as Peacekeeping operations; eradicate the suppression of women's rights, eradicate domestic violence, rape, and sexual harassment, (2). women play a role in empowering women, improving the economy of women (3) Female gender (Female Peacekeepers) who play a role in security for prevention. While the role of women's gender in realizing sustainable development is: (a) The role of promoting gender equality, increasing gender equality, increasing women's welfare. (b) Increasing women's welfare, both in the economic and political spheres and providing operational assistance in efforts to empower women.